Effects of a lifestyle intervention on body composition in prostate cancer patients on androgen deprivation therapy. Issue 2 (26th May 2020) - Chaplow, Zachary L.; Focht, Brian C.; Lucas, Alexander R.; Grainger, Elizabeth; Simpson, Christina; Buell, Jackie; Fairman, Ciaran M.; Thomas‐Ahner, Jennifer M.; Bowman, Jessica; DeScenza, Victoria R.; Monk, J. Paul; Mortazavi, Amir; et al.
Abstract: Background: Exercise and dietary (EX+D) interventions could represent an optimal treatment for attenuating or reversing adverse effects of androgen deprivation therapy (ADT) in prostate cancer (PCa) patients. The Individualized Diet and Exercise Adherence‐Pilot (IDEA‐P) trial compared the effects of an EX+D intervention relative to standard‐of‐care (SC) treatment among PCa patients undergoing ADT. The present study evaluated the effects of the EX+D intervention on body composition (BC) obtained via dual‐energy X‐ray absorptiometry (DXA) in a subsample of IDEA‐P patients. A secondary objective was to explore the association of adiposity and lean mass with mobility performance and strength. Methods: Complete DXA data were acquired from a subsample of 22 PCa patients (EX+D: n  = 13; SC: n  = 9) at baseline and 3 month follow‐up. Intention‐to‐treat analysis included data from 30 participants ( M age = 66.28; SD = 7.79) with baseline DXA assessments. Results: Intention‐to‐treat analysis revealed EX+D resulted in significant improvements in fat mass ( P  = 0.022), per cent fat mass ( P  = 0.028), trunk fat mass ( P  = 0.017), fat mass/lean mass ( P  = 0.040), and per cent lean mass ( P  = 0.026) vs. SC. EX+D also resulted in more favourable changes in appendicular lean mass/body mass ( d  = 0.59). Select BC outcomes were also significantly correlated with mobility performance and strength ( P  < 0.05) at 3 month follow‐up. Conclusions: Findings suggest the EX+D intervention resulted in superior preservation of lean tissue and improvement in adiposity relative to SC treatment. Results underscore the utility of implementing EX+D interventions for preserving muscle mass and reducing adiposity in PCa patients undergoing ADT.